Die morphologisch-tektonische Gliederung Costa Ricas (Mittelamerika). Bericht über neue Karten und ihre Interpretation - Weyl, Richard (ERDKUNDE, 1971)
A newly published relief map and a similarly new geological map of the Central American republic of Costa Rica allow together with geological investigations in recent years, an attempt to devise a morpho-tectonic division of the country. The most prominent features in the area are: I. The Peninsulas of the Pacific Coast. II. The Pacific Lowlands and Coastal Plains. III. The Pacific Coastal Range. IV. The General- and Goto Brus-Valley. V. The Talamanca-Range. VI. The Central Valley. VII. The Tilaran-Range. VIII. The volcanic chain of the Central Cordillera. IX. The volcanic chain of Guanacaste. X. (The volcano Chiriqui in Panama). XI. The Limon Basin.